2018
DOI: 10.1007/s00436-018-5979-3
|View full text |Cite
|
Sign up to set email alerts
|

Behavior of two Leishmania infantum strains—evaluation of susceptibility to antimonials and expression of microRNAs in experimentally infected J774 macrophages and in BALB/c mice

Abstract: Strains of the same Leishmania parasite species, isolated from different host organisms, may exhibit unique infection profiles and induce a change in the expression of microRNAs among host macrophages and in model host mice. MicroRNAs (MiR) are endogenous molecules of about 22 nucleotides that are involved in many regulatory processes, including the vertebrate host immune response. In this respect, the infectivity and susceptibility to antimonials of two L. infantum strains, BH46, isolated from human, and OP46… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 46 publications
0
9
0
Order By: Relevance
“…Differential expression of miR 122 was demonstrated in mice macrophages infected by L . infantum [31], in human macrophages, infected by L . donovani , members of the miR 30A-3p family were misregulated [15], suggesting that there is variation in miRNA response to Leishmania spp.…”
Section: Discussionmentioning
confidence: 99%
“…Differential expression of miR 122 was demonstrated in mice macrophages infected by L . infantum [31], in human macrophages, infected by L . donovani , members of the miR 30A-3p family were misregulated [15], suggesting that there is variation in miRNA response to Leishmania spp.…”
Section: Discussionmentioning
confidence: 99%
“…36 Silva et al showed alterations in the miR-155 level probably contributes to the regulation of responses to Leishmania infantum. 37 In their research, Singh et al presented the current modulatory contribution of the host microRNA (miR30a-3p) in regulating the host cell macroautophagy/autophagy following the infections with L. donovani. 19 Wendlandt demonstrated that logarithmic phase of promastigote multiplying processes, different miRNAs, such as miR-200b, let-7b, miR-339-5p, miR-423-5p, and miR-744, noticeably changed in the infected macrophages.…”
Section: Discussionmentioning
confidence: 99%
“…infantum promastigotes cultivated in Grace’s medium demonstrated a lower percentage of infected macrophages but high parasite load (as shown by optical microscopy and flow cytometry analysis). This can be explained by the nature of the medium which is largely used in many studies to induce infection in animal models (da Silva Jr. et al 2015 ; Silva et al 2018 ; Siripattanapipong et al 2019 ). Based on our data, we can suggest that Grace’s medium, instead of inducing procyclic promastigotes, probably induces the formation of metacyclic promastigotes that explains the high parasite load in the infected macrophages in vitro.…”
Section: Discussionmentioning
confidence: 99%